Labor exploitation in the Italian agricultural sector: the case of vulnerable migrants in Tuscany - Caterina Francesca Guidi; Fabio Berti (Frontiers in Sociology, 2023)
Labor exploitation of agricultural migrant workers is a well-documented phenomenon by investigations and field research in several Italian regions, both in the North and the South. Despite the agri-food excellencies of the “Made in Italy” brand being a source of pride for Italian entrepreneurship, including the viticulture sector, evidence shows that many of these products are the result of different levels of illegal recruitment and labor exploitation. In this article, the authors analyze the impact of recent waves of vulnerable migrants entering the Italian labor market and present the results of a qualitative field research, conducted in Tuscany between 2021 and 2022. Through 60 interviews with exploited migrant workers and 40 interviews with relevant stakeholders, the authors focus on the recruitment process of vulnerable migrants into the agriculture sector and the labor conditions granted to them regardless of their particular migratory status. The article concludes with the analysis of the peculiarities of the Tuscan case study, characterized by the presence of a legal system of labor exploitation.